Model for alkali-silica reaction expansions in concrete using zero-thickness chemo-mechanical interface elements. (15th December 2020) - Liaudat, Joaquín; Carol, Ignacio; López, Carlos M.
Abstract: Alkali-Silica Reaction (ASR) is a particular type of chemical reaction in concrete, which produces cracking and overall expansion of the affected structural element due to the formation of expansive reaction products within the cracks. This paper develops the formulation of a coupled Chemo-Mechanical (C-M) Finite Element (FE) model for simulating ASR expansions in soda-lime glass concrete at the meso-scale. The model considers several C-M coupling mechanisms, including a reaction-expansion mechanism qualitatively proposed by the authors elsewhere on the basis of experimental results, which is introduced in order to reproduce the effect of compressive stresses on the development of ASR expansions. The model has the characteristic ingredient of using zero-thickness interface elements for modelling the C-M mechanisms leading to the propagation of cracks due to the formation of ASR products within them. This fact has required the development of: (i) a new FE formulation for diffusion-reaction processes occurring within discontinuities represented by interface elements, and (ii) a new mechanical constitutive law for interface elements, which is able to reproduce the propagation of a crack induced by the development of an internal pressure exerted by solid reaction products formed within it. In addition, the numerical implementation of the diffusion-reaction formulation has been advantageously performed with clear separation between the boundary-value or 'structural' governing equations (i.e. continuity and concentration gradient relations), and the 'constitutive' (i.e. chemical) equations. The model is illustrated with some application examples.